Investigation of the response of sweet cherries to root mycorrhisation with biologics for sustainable horticulture development - Gerasko, Tetyana; Герасько, Тетяна Володимирівна; Tymoshchuk, Tetiana; Sayuk, Oleksandr; Rudenkо, Yurii; Mrynskyi, Ivan (Ukraine, Zhytomyr, 2023)
EN: Sustainable horticulture development is a priority area considering climate change, especially in the context of reduced water supply. The search for ways to regulate the resistance of fruit trees to stressors is an urgent issue for the world community. The use of beneficial microorganisms to inoculate plant roots helps reduce the use of synthetic substances and is an alternative for sustainable horticulture. The purpose of the study is to identify the specific features of the effect of root inoculation by mycorrhizal fungi on the reaction of sweet cherries to develop strategies for managing the production of fruit products. The study was conducted during 2018-2020 in the sweet sweet cherry orchard of the southern steppe subzone of Ukraine. Such research methods as field, laboratory, biochemical, physiological, and statistical were used. The regularities of the influence of mycorrhizal fungi on the total moisture content and water-holding capacity of sweet cherry leaves were examined. In the first year of studies on endomycorrhizal root inoculation, these indicators were higher compared to the control group. The positive effect of endo-ectomycorrhiza on the water-holding capacity of sweet cherry leaves was elucidated. The total leaf surface and the content of green pigments in the leaves were determined as one of the main indicators of the photosynthetic potential of a fruit crop. The effect of inoculation of sweet cherry roots by mycorrhizal fungi on the ratio of chlorophylls (a/b) in leaves was established. The parameters of the content of total nitrogen, phosphorus, and potassium in sweet cherry leaves were determined. The use of mycorrhizal fungi increases the adaptive properties of sweet cherry trees to stressful factors, namely, arid conditions in the south of Ukraine. The research results can be used by fruit producers to improve climate-optimised technologies, which will substantially reduce risks and possible economic losses, and preserve biodiversit. /// UA: Стійкий розвиток садівництва є пріоритетним напрямом за зміни клімату, особливо в умовах зменшення вологозабезпечення. Пошук шляхів регуляції стійкості плодових дерев до стресорів є актуальним питання для світової спільноти. Використання корисних мікроорганізмів для інокуляції коренів рослин сприяє зменшенню застосування синтетичних речовин і є альтернативою для стійкого садівництва. Метою досліджень було з’ясувати особливості впливу інокуляції коренів мікоризними грибами на реакцію черешні для розробки стратегій управління виробництвом плодової продукції. Дослідження проводили протягом 2018-2020 рр. у черешневому саду Південної степової підзони України. Використані такі методи досліджень, як польовий, лабораторний, біохімічний, фізіологічний і статистичний. Досліджено закономірності впливу мікоризних грибів на загальний уміст вологи та водоутримувальну здатність листків черешні. У перший рік досліджень за інокуляції коренів ендомікоризою ці показники були вищими порівняно з контролем. З’ясовано позитивний вплив ендо-ектомікоризи на водоутримувальну здатність листків черешні. Визначено загальну листкову поверхню і уміст зелених пігментів у листі, як одних із основних показників фотосинтетичного потенціалу плодової культури. Встановлено наслідки інокуляції коренів черешні мікоризними грибами на співвідношення хлорофілів (a/b) у листках. Визначено параметри умісту загального азоту, фосфору і калію у листках черешні. Використання мікоризних грибів забезпечує підвищення адаптаційних властивостей дерев черешні до стресових чинників, а саме посушливих умов Півдня України. Результати досліджень можуть бути використані виробниками плодової продукції для удосконалення кліматично оптимізованих технологій, що забезпечить суттєве зменшення ризиків, можливих економічних втрат і збереження біорізноманіття.
Дослідження реакції черешні на мікоризацію коренів біопрепаратами для стійкого розвитку садівництва
Keywords: endomycorrhiza; ectomycorrhiza; leaf area; Prunus avium; water-holding capacity; chlorophyll; basic elements of nutrition; ендомікориза; ектомікориза; площа листя; водоутримувальна здатність; хлорофіл; основні елементи живлення